Capital controls and capital flow volatility during global shocks: Indian experience - Kumar, Sujit (Asian Journal of Economics and Empirical Research, 2023)
This paper examines the issue of capital controls in India and their effectiveness in stabilizing the capital flow volatility in the economy. It documents the evolution of the capital controls regime in India since its economic liberalization in 1991 and focuses on India’s experience with capital controls in the period leading up to the Global Financial Crisis (GFC) of 2008 until the taper tantrum aftermath in 2013. We construct a capital controls index based on data from the IMF’s Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER). The index shows careful ease of capital controls by Indian policymakers in the financial sectors, i.e., the capital market, money market and direct investment, over the 2001–2008 period. The index further shows that the process of decontrol in the capital market stagnated during 2009–2014 due to the GFC to insulate the Indian economy from global shocks. This paper further explores the impact of capital controls in managing capital flow volatility in the context of the GFC. Using the tobit estimation approach, we show that capital controls effectively reduce capital flow volatility in the pre-GFC period followed by a limited impact post-GFC. This complements the capital account liberalization process during pre-GFC period. Our findings support India’s prudent approach to capital account management as financial markets evolve to manage risk efficiently in a large economy.